2018
DOI: 10.1111/1759-7714.12869
|View full text |Cite
|
Sign up to set email alerts
|

Location of stage I–III non‐small cell lung cancer and survival rate: Systematic review and meta‐analysis

Abstract: BackgroundThe association between the location of non‐small cell lung cancer (NSCLC) and prognosis is a debated issue. Some studies have provided evidence of better prognosis of upper lobe tumors than lower to middle lobe tumors, while other studies have reported contrasting conclusions. The aim of this study was to further assess this association through a systematic review and meta‐analysis.MethodsMedline, Embase, and the Cochrane Central Register of Controlled Trials were searched up to 27 January 2017. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 37 publications
6
35
0
Order By: Relevance
“…To our surprise, we found that the primary site and surgery type could affect the prognosis. Similar results were also obtained in a published meta-analysis ( 26 ). In another study, the results showed no significant difference in OS between lesions located in the upper/middle and lower lobes ( 27 ).…”
Section: Discussionsupporting
confidence: 89%
“…To our surprise, we found that the primary site and surgery type could affect the prognosis. Similar results were also obtained in a published meta-analysis ( 26 ). In another study, the results showed no significant difference in OS between lesions located in the upper/middle and lower lobes ( 27 ).…”
Section: Discussionsupporting
confidence: 89%
“…The primary site of tumour was an important predictor of overall survival in the patients without metastasis in our study. It supports the ndings of previous studies, which reported that upper lobe tumours were associated with better survival compared to those located in other sites of the lung 17,35 . Our study also revealed an association between tumours in the main bronchus and poorer overall survival compared to the upper lobe tumours.…”
Section: Discussionsupporting
confidence: 91%
“…Extent of lymph node dissection was not considered for either lobar or sublobar resection, and as mentioned previously, there was no consideration to lobe or segment in the analysis. Previous work has found that lower lobe origin of NSCLC confers worse mortality 19,20 . We found that there was no difference between lower lobectomy for superior segment tumors or superior segmentectomy for OS, DFS, LRFS.…”
Section: Discussionmentioning
confidence: 38%